Efficacy of early enteral nutrition support on the nutritional status of patients after gallstone surgery - Fang Wang; Yun Gao (PLoS ONE, 2025)
Objective To evaluate the overall efficacy of early enteral nutrition support on the nutritional status of patients following gallstone surgery, providing a theoretical basis for its application in postoperative care. Methods A retrospective analysis was conducted on 98 hospitalized patients who underwent gallstone surgery between February 2021 and March 2023. The patients were divided into two groups: the study group, which received early nutritional intervention, and the control group, which started nutritional support three days post-surgery. The primary objective was to assess nutritional status, while secondary objectives included gastrointestinal function, immune function markers, and the incidence of postoperative and gastrointestinal complications. Nutritional status, gastrointestinal function, immune function, and complications were compared between the two groups before and one week after intervention. Results After the intervention, the study group showed significantly higher levels of total protein (TP), prealbumin (PAB), albumin (ALB), transferrin (TF), and body mass index (BMI) compared to the control group (P<0.05). Additionally, the scores for Nutrition Risk Screening 2002 (NRS 2002) and the Malnutrition Universal Screening Tool (MUST) were notably lower in the study group (P<0.05). Postoperatively, the study group experienced shorter times to first exhaust, defecation, bowel sound recovery, first meal, and overall hospital stay compared to the control group (P<0.05). Although the pre-intervention levels of CD3+, CD4+, CD8+, and CD4+/CD8+ were comparable between the groups (P>0.05), these immune markers were significantly higher in the study group post-intervention (P<0.05). The incidence of both postoperative and gastrointestinal complications was significantly lower in the study group than in the control group (both P<0.05). Conclusion Early enteral nutrition support significantly improves the nutritional status of patients after gallstone surgery, enhances gastrointestinal and immune function, and reduces the occurrence of complications. These findings underscore its clinical significance and value in postoperative care.